Analysis of the Pastor's Leadership in Instilling Christian Values in the GSJA CLC Congregation - Olivia Sri Simanullang; Kristiani Della Manurung; Elly Fadilla Siregar; Zuhro Tamanna Daulay; Flores Tanjung (Universitas Dharmawangsa Medan, 2025)
This study aims to analyze in depth the role and effectiveness of pastoral leadership in the process of instilling Christian values in the congregation at the City Life Center Assemblies of God Church (GSJA CLC). Christian values are an essential foundation for the congregation's spiritual and moral growth, and the pastor's leadership plays a key role as a role model, teacher, and motivator. The research method used is descriptive qualitative with a case study approach. Data collection was conducted through in-depth interviews with the pastor and congregation representatives, participant observation, and analysis of internal church documents related to the development and teaching programs.